Resposta da comunidade de microliquens corticícolas a fatores ambientais em duas fitofisionomias - Menezes, Aline Anjos de (2013)
Lichens are the result of the association between a fungal species and an algae and/or cyanobacteria. Lichens have preferences with respect to certain environmental factors that may be related to the structure and diversity of the habitat, enabling their occurrence on in various substrates and environments. The objective of this work was to analyze the species richness and composition of corticolous microliquens in the understory of two vegetation types (Cerradão and Carrasco) in the Chapada do Araripe, Ceará, and also to study the effect of environmental factors such as light, pH of the substrate, altitude and BHD (breast height diameter) of the in relation to lichen species richness and composition. The following hypotheses were tested: (H1) The study areas differ in their richness of corticicolous microliquens; (H2) the study areas differ in their composition of corticicolous microliquens; (H3) areas with higher light intensity have greater diversity of corticicolous microliquens; (H4) areas with higher altitudes have greater diversity of corticicolous microliquens; (H5) phorophytes with lower pH exhibit greater diversity of corticicolous microliquens and (H6) phorophytes with higher BHD exhibit greater diversity of corticicolous microliquens. The study was conducted in two collecting expeditions between 2011 and 2012, in which we used opportunistic colleting (first expedition) and the demarcation of a transect of 200 m, with 10 points per area (second expedition). At each point within a radius of 2 m, all phorophytes with CAP between 5-30 cm were analyzed, with the microliquens collected within 1.5 meters along the stem (tree trunk) from the ground level. Among the 1,300 collected samples, a total of 189 species were identified in 60 genera and 17 families. All species are new records for the state of Ceará, 11 species are reported for the first time to the Northeast, 13 are new records for Brazil and a species is new for South America. Additionally, ten species are described as new to science. Carrasco area was richer in lichen species richness than the Cerradão, although they showed similar species compositions. BHD was not significant in the analysis as well all the studied in relation to vegetation types. The environmental factors altitude, pH, total transmittance and canopy openness had significant effects on lichen species richness. Given the limited number of studies on ecology and diversity of corticicolous microlichens in Northeastern Brazil, the present study is relevant to the knowledge of the liquenized mycota of the studied region, and Brazilian country.